ANALISIS PENGGUNAAN TEKNIK KOREKSI TEMAN SEJAWAT DALAM PEMBELAJARAN MENULIS TEKS EKSPOSISI - Fika Puspita Sari; Agus Setyonegoro; Priyanto Priyanto (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
The purpose of this study was to determine the planning and implementation of the friend correction technique in the learning to write expository texts of class VIII students of SMPN 25 Jambi City. This research is qualitative and descriptive. Data and data sources in this study used primary data (observation of the learning process) and secondary data (student work). Using the purposive sampling technique Data collection techniques include observation, interviews, and documentation. Data analysis in this study includes data reduction, data presentation, and conclusions. The results of this study indicate that the planning and implementation went well, so that the application of peer correction techniques can improve the quality of the learning process of writing exposition texts for students.